Recovery from TBT pollution in English Channel environments: A problem solved?. Issue 2 (30th June 2015) - Langston, W.J.; Pope, N.D.; Davey, M.; Langston, K.M.; O' Hara, S.C.M.; Gibbs, P.E.; Pascoe, P.L.
Highlights: TBT in the Channel region was monitored in water, sediment and clams over 25 years. Two 'hotspots' were singled out for study – Poole Harbour and Southampton Water. Contamination has decreased following TBT removal from leisure and commercial craft. Recovery of clams is linked to decline of TBT pollution following regulatory measures. Dogwhelk recovery is widespread but delayed at some sites by shipping impacts. Abstract: Following recognition of effects in the 1980s, tributyltin (TBT) has been monitored at sites in the English Channel to evaluate the prognosis for biota – spanning the introduction of restrictions on TBT use on small boats and the recent phase-out on the global fleet. We describe how persistence and impact of TBT in clams Scrobicularia plana has changed during this period in Southampton Water and Poole Harbour. TBT contamination (and loss) in water, sediment and clams reflects the abundance and type of vessel activity: half-times in sediment (up to 8y in Poole, 33y in Southampton) are longest near commercial shipping. Recovery of clam populations – slowest in TBT-contaminated deposits – provides a useful biological measure of legislative efficacy in estuaries. On rocky shores, recovery from imposex in Nucella lapillus is evident at many sites but, near ports, is prolonged by shipping impacts, including sediment legacy, for example, in the Fal.